P09.02 Mapping and tackling tumor and chemotherapy-induced immune suppression in breast cancer sentinel lymph nodes. (1st October 2020) - Prokopi, N; Heeren, M; Milenova, I; van Pul, K; Muijlwijk, T; Arends, M; van der Velde, S; Vrijland, K; van Weverwijk, A; de Visser, K; van de Ven, R; de Gruijl, T
Abstract : Background: Breast cancer (BrC) is the most prevalent cancer in women worldwide. Unfortunately, still limited treatment options are available for the most aggressive subtypes (i.e. hormone receptor [HR] negative). The response to neoadjuvant chemotherapy (NACT) in patients with HR-negative BrC can in part be influenced by an effective anti-tumor immune response. The sentinel lymph node (SLN) is the first site where BrC-specific T cell priming will occur but unfortunately it is also a major target of BrC-induced immune suppression. Lymph-node resident dendritic cells (LNR-DC) were found to be suppressed in metastatic SLN. 1 In addition, this tumor-mediated immune suppression of LNR-DC is related to high-risk triple-negative BrC and may be a negative predictor for prognosis 1 . Preliminary data showed that NACT further reduced the activation status of LNR-DC. The goal of this study is to identify immune-enhancing agents that can counteract the tumor-mediated immune suppression of LNR-DC and promote tumor-specific T cell responses in order to improve therapy outcome in BrC patients upon NACT. Materials and Methods: Phenotypic analyses were performed on immune-cell subsets in human BrC SLN using multi-color flow cytometry. In addition, ex-vivo cultures with human BrC SLN-derived cells and in vivo mouse experiments were performed to study the therapeutic efficacy of Toll-like receptor (TLR)-ligands (R848 and CpG) and a STING-ligand (STING-L; 2'3'-c-di-AM(PS)2 (Rp, Rp)). Results: Higher rates of LNR-DCs, but with an apparently reduced activation state, were found in SLN of NACT-treated patients compared to patients treated with surgery only. A comparative ex-vivo study with SLN cultures on the effects of R848, CpG-B and STING-L showed R848 to be superior in terms of LNR-DC activation. In a Krt14 (K14)-cre;Cdh1F/F;Trp53F/F (KEP) BrC mouse model, the effects of intratumoral administration of TLR- and STING-L were determined in combination with doxorubicin. STING-L outperformed R848 and CpG-B in terms of controlling primary tumor growth. Of note, in human e x-vivo cultures CpG-B proved effective in LNR-DC activation when combined with a STAT3 inhibitor, leading to the boosting of mammaglobin-specific T cell responses, Th1 skewing, and a drop in CpG-induced Treg levels. Conclusions: In summary, intratumoral delivery of TLR- and STING-ligands in combination with NACT might be an interesting therapeutic approach in patients with high-risk HR-negative BrC, leading to SLN potentiation and enhanced antitumor T cell immunity. Future clinical studies should demonstrate the therapeutic benefit of this approach. Reference: van Pul, et al . 2019, Journal for ImmunoTherapy of Cancer . Disclosure Information: N. Prokopi: None. M. Heeren: None. I. Milenova: None. K. van Pul: None. T. Muijlwijk: None. M. Arends: None. S. van der Velde: None. K. Vrijland: None. A. van Weverwijk: None. K. de Visser: None. R. van de Ven: None. T. de Gruijl: None.